PENGARUH TUTOR SEBAYA TERHADAP MOTIVASI BELAJAR SISWA DI SMP NEGERI SUNGGUMINASA KABUPATEN GOWA - ., Kartini (Makassar Journal of Social Sciences, 2015)
Abstract This study aims to determine the application of peer tutors Junior High School, students 'motivation Sungguminasa class and to determine the presence or absence of the influence of peer tutoring to students' motivation SMP Sungguminasa. Research conducted with quantitative descriptive statistical approach. The research variables consisted of peer tutors (variable X) and motivation to learn (variable Y). The study population was as many as 560 students and a sample of 56 people. The data collection techniques are observation, questionnaires, interviews and documentation. Data analysis techniques performed by descriptive statistical analysis and statistical analysis infrensial. Based on the results of this research is that peer tutors picture falls into the category of "good" and a picture of student motivation included in the category of "good". As well as the hypothesis was accepted by the peer tutors statement effect on students' motivation SMP Sungguminasa.